Karakterisasi Asap Cair Hasil Pirolisis Sampah Styrofoam Dengan Katalis Zeolite - Olke Wisje Lumingkewas; I Dewe Ketut Anom; Ardi Kapahang (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
The purpose this achieved in this research is 1.To get a few percent of liguid smoke products acquired from the pyrolysis of Styrofoam waste. 2.To know the effect of using zeolite in the waste pyrolysis process styrofoam to the speed of formation of liquid smoke product .3. To characterize the physical and chemical properties of liquid smoke from pyrolysis of syrofoam wast. The research method used to convert Styrofoam waste into liquid smoke is the pyrolisis method. For characterize of liquid smoke from pyrolysis using equipment: a set of pyrolysis tools, Fenske Viscometer Oswald, Picnometer, Boilling Point Meter and a set of KG-SM alloy. The results showed that the pyrolysis of 100 grams of Styrofoam wa ste using zeolite catalyst produced an average of 69,33% liquid smoke whereas the pyrolysis of Styrofoam waste without using a catalyst produces average 61,67 % liquid smoke. Time and temperature of pyrolysis have the same influence, the higher value, the more liquid smoke is produced. the length of ime for pyrolysis of styrofoam waste uing zeolite catalyst laste for 4,5 hours, while the pyrolysis of Styrofoam without a catalyst laste for 3,5 hours. Based of the physical ang chemical properties of liquid smoke, the pyrolysis of Styrofoam waste using a catalyst or without using a catalyst can both be classified into gasoline.